73 Is There A Real Relationship Between Body Mass Index and Vasovagal Syncope or is it Just Anecdote?. (6th February 2020) - Cohen, S; Young, E; Hunt, S; Garimella, S; Lakhani, D R
Abstract: Introduction: Syncope is characterised by global cerebral hypoperfusion rapidly causing a transient loss of consciousness with loss of voluntary muscle tone and a subsequent spontaneous, prompt and complete recovery. It is often caused by Neurally mediated reflex syncope syndromes of which Vasovagal syncope (VVS) is the commonest form. The prodromal symptoms of VVS are explained by circulatory alterations (vasodilatation and bradycardia) and autonomic activation. Whilst many triggers and risk factors for such alterations are recognised, they are incompletely understood. Anecdotally, being "young and thin" is a risk factor but there is little published data evaluating the relationship between body weight and VVS. Whilst VVS can often be diagnosed on clinical history alone, further evaluation is warranted in some patients. The validated test to assess susceptibility to VVS is the head-up-tilt table (HUT) test. We set out to evaluate the relationship between Body Mass Index (BMI) and the outcome of HUT testing. Methods: We reviewed the outcomes of 1193 patients attending for HUT testing at the University Hospitals of Leicester between December 2014 and October 2017. The protocol used was a 40 minute passive HUT (70 degree) followed by sublingual nitroglyserin. The parameters of height, weight, gender and test outcome were recorded prospectively and interrogated retrospectively. Results: Of the 1193 patients, the passive HUT test was positive for VVS in 293 patients. These patients were then sub-grouped by BMI as set out in the table. The chances of VVS, as diagnosed by HUT testing are almost doubled in those with a (clinically underweight) BMI range 16-20. (p value 0.002-0.001) Discussion: The presented data supports the anecdotal experience of many clinicians: that low BMI may be associated with an increased tendency to VVS. The physiological basis for this (if it is real) is not understood and requires further evaluation since it may have implications for future management strategies. Larger studies are required to further analyse this relationship to determine if BMI is an independent predictor or risk factor for VVS.